1992
DOI: 10.1577/1548-8675(1992)012<0667:robhth>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Blueback Herring to High-Frequency Sound and Implications for Reducing Entrainment at Hydropower Dams

Abstract: Low‐ and high‐frequency sounds were tested as a means of repelling blueback herring Alosa aestivalis in confined‐area and open‐water experiments. Confined‐area tests were performed by analyzing the response of blueback herring in floating net‐pens to sounds differing in frequency, sound pressure levels (SPLs, given in decibels [dB] in reference to l.0 μPa), and pulse width. Highfrequency sounds between 110 and 140 kHz, at SPLs above 180 dB (at 1.0 m from the transducer) and at various pulse widths, elicited st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
47
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 14 publications
1
47
0
Order By: Relevance
“…Steam or hydro-powered electricity generating stations often entrain and kill fish and can therefore have a negative impact on fish populations. High frequency sounds emitted by transducers used at dams have been shown to reduce the entrainment of A. aestivalis and A. pseudoharengus for short periods of time [9]. Applying high intensity pulsed ultrasound (frequencies from 110-140kHz at power levels above 180dB) has been shown to repel several species of Clupeiformes, including A. sapidissima, A. aestivalis and A. pseudoharengus, from cold water intakes used in power plants.…”
Section: Introductionmentioning
confidence: 99%
“…Steam or hydro-powered electricity generating stations often entrain and kill fish and can therefore have a negative impact on fish populations. High frequency sounds emitted by transducers used at dams have been shown to reduce the entrainment of A. aestivalis and A. pseudoharengus for short periods of time [9]. Applying high intensity pulsed ultrasound (frequencies from 110-140kHz at power levels above 180dB) has been shown to repel several species of Clupeiformes, including A. sapidissima, A. aestivalis and A. pseudoharengus, from cold water intakes used in power plants.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the early 1990s it was reported that ultrasonic sonar pulses were an efficient way of repelling certain clupeiform fish species from the water intakes of power plants (Dunning et al, 1992;Nestler et al, 1992). It was not clear whether the fish responded to the ultrasonic component of the sonar or whether they responded to low frequency by-products.…”
Section: Introductionmentioning
confidence: 99%
“…In fisheries, sound has been applied to drive fishes into nets, and attracting fishes using sound has been tried [2][3][4] . It is also possible to keep fish away from a certain area (e.g., a water intake opening of a power plant) using sound [5][6][7][8][9] . Moreover, the strong ability of associate learning in fish allows conditioning procedures to be applied for fish aggregations using sound in aquaculture 10).…”
Section: Introductionmentioning
confidence: 99%